(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The paper analyzes the various ills faced by refugees over time in the face of various international violations that intensify major exoduses throughout the world. Based on doctrines and based on the hypothetical-deductive method, it was reflected in the juridical possibilities for these rights to cease to be violated and finally to be minimally effective, from the social inclusion of the refugees. Through the research, the possibility of minimal enforcement was found through agencies such as the United Nations High Commissioner for Refugees (UNHCR), the United Nations Office of the United Nations and the National Council of Refugees (CONARE), for example.